Material characterization of blended sisal-kenaf composites with an ABS matrix. (October 2017) - Dunne, R.; Desai, D.; Sadiku, R.
Abstract: Natural fibre-based materials are becoming a valid alternative to traditional synthetic based products for composite reinforcing and sound attenuating treatments. In recent years, natural fibres have been used more frequently in the development of structural components and sound absorbing panels due to their low density, low cost and environmentally-friendly attributes. Based on a literature review of previous studies on natural fibres and their application in the automotive industry, this work investigates the mechanical characterization of various natural fibre composites with an Acrylonitrile Butadiene Styrene matrix (ABS). According to the literature review and the knowledge of the authors, the ratios of fibre and ABS presented have not yet been investigated. The tensile strength, impact strength and air flow resistivity of samples with different densities have been measured, and have been found to vary. In the conclusion some suggestions for the use of these natural fibre composites, for automotive applications, are reported.